Systematic Experimental Evaluation of Submilliwatt PV Cells for Indoor Applications - Eduard Ferré; Marc Azlor; Manel Gasulla; Ferran Reverter (Proceedings)
In the context of energy harvesting for tiny autonomous sensors placed indoors, this work carries out a systematic experimental evaluation of low-power, low-area photovoltaic (PV) cells. The evaluation involves several cell technologies and types of illumination and, for each technology–illumination pair, a sweep of different levels of illuminance and temperature expected indoors is performed. The information extracted from this work will enable a better selection of the cell technology for a given type of indoor illumination, and a better design of the ensuing maximum power point (MPP) tracker oriented to the cell technology–illumination pair.